Synchronous versus sequential chemo-radiotherapy in patients with early stage breast cancer (SECRAB): A randomised, phase III, trial. (January 2020) - Fernando, Indrajit N.; Bowden, Sarah J.; Herring, Kathryn; Brookes, Cassandra L.; Ahmed, Ikhlaaq; Marshall, Andrea; Grieve, Robert; Churn, Mark; Spooner, David; Latief, Talaat N.; Agrawal, Rajiv K.; Brunt, Adrian M.; et al.
Highlights: SECRAB is the largest chemo-radiotherapy trial to date in early breast cancer. SECRAB showed a positive therapeutic benefit of using adjuvant synchronous chemo-radiotherapy. Synchronous chemo-radiotherapy should be used for ≤ 3 week radiotherapy schedules. SECRAB results are applicable to patients having CMF or anthracycline-CMF schedules. Overall survival outcome may increase for patients receiving synchronous anthracycline-CMF. Summary: Background: The optimal sequence of adjuvant chemotherapy and radiotherapy for breast cancer is unknown. SECRAB assesses whether local control can be improved without increased toxicity. Methods: SECRAB was a prospective, open-label, multi-centre, phase III trial comparing synchronous to sequential chemo-radiotherapy, conducted in 48 UK centres. Patients with invasive, early stage breast cancer were eligible. Randomisation (performed using random permuted block assignment) was stratified by centre, axillary surgery, chemotherapy, and radiotherapy boost. Permitted chemotherapy regimens included CMF and anthracycline-CMF. Synchronous radiotherapy was administered between cycles two and three for CMF or five and six for anthracycline-CMF. Sequential radiotherapy was delivered on chemotherapy completion. Radiotherapy schedules included 40 Gy/15F over three weeks, and 50 Gy/25F over five weeks. The primary outcome was local recurrence at five and ten years, defined as time to local recurrence, and analysed by intention to treat. ClinicalTrials.gov NCT00003893. Findings: Between 02-July-1998 and 25-March-2004, 2297 patients were recruited (1150 synchronous and 1146 sequential). Baseline characteristics were balanced. With 10.2 years median follow-up, the ten-year local recurrence rates were 4.6% and 7.1% in the synchronous and sequential arms respectively (hazard ratio (HR) 0.62; 95% confidence interval (CI): 0.43–0.90; p = 0.012). In a planned sub-group analysis of anthracycline-CMF, the ten-year local recurrence rates difference were 3.5% versus 6.7% respectively (HR 0.48 95% CI: 0.26–0.88; p = 0.018). There was no significant difference in overall or disease-free survival. 24% of patients on the synchronous arm suffered moderate/severe acute skin reactions compared to 15% on the sequential arm ( p < 0.0001). There were no significant differences in late adverse effects apart from telangiectasia ( p = 0.03). Interpretation: Synchronous chemo-radiotherapy significantly improved local recurrence rates. This was delivered with an acceptable increase in acute toxicity. The greatest benefit of synchronous chemo-radiation was in patients treated with anthracycline-CMF. Funding: Cancer Research UK (CR UK/98/001) and Pharmacia.